Esthetics in implant-supported prostheses: a literature review - Délben, Juliana [UNESP]; Goiato, Marcelo [UNESP]; Gennari Filho, Humberto [UNESP]; Assunção, Wirley [UNESP]; Santos, Daniela dos [UNESP] (American Academy of Implant Dentistry, 2011)
Esthetics is important for success of implant-supported prostheses. This study aimed to review esthetics concepts for implant treatment. Research in the PubMed database included studies published from 1995 to 2010 with the keywords implant esthetics, implant-supported prostheses, and esthetics. Forty-five studies were evaluated regarding the presurgical planning, surgical phase, and temporary and final restoration phases. It was concluded that esthetics in implant-supported prostheses results from a multidisciplinary approach from planning until insertion of the final restoration.
Keywords: Dental implant; Implant-supported prosthesis; Esthetics